2022
DOI: 10.1111/jcap.12366
|View full text |Cite
|
Sign up to set email alerts
|

The associations between reading mind in the eyes abilities, alexithymia, empathy, and bullying behavior in Turkish adolescents

Abstract: Problem The development of any program to reduce bullying is possible with a better understanding of the associated underlying factors with its emergence. This study, therefore, aimed to investigate three different social cognitive abilities: abilities to read minds in the eyes, alexithymic personality traits, and empathy, in association with bullying behaviors in adolescents. Although these factors have been studied separately, our data highlighted their effect, relationship, and interconnectivity. Methods Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…This is supported by a systematic review [56] that examined twelve studies, ten of which suggested that the deficits in the processing of emotional facial expressions in individuals with high alexithymic traits extended to all emotional categories (including anger, fear, sadness, happiness and neutral stimuli). High alexithymic traits have been linked with deficits in cognitive empathy [35,57] and affective empathy [55,58] while some studies [e.g., 58,59] suggest that high alexithymic traits are associated predominantly with low cognitive empathy, while affective empathy is less affected, indicating more research is needed.…”
Section: Alexithymic Traits and Facial Emotion Recognitionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by a systematic review [56] that examined twelve studies, ten of which suggested that the deficits in the processing of emotional facial expressions in individuals with high alexithymic traits extended to all emotional categories (including anger, fear, sadness, happiness and neutral stimuli). High alexithymic traits have been linked with deficits in cognitive empathy [35,57] and affective empathy [55,58] while some studies [e.g., 58,59] suggest that high alexithymic traits are associated predominantly with low cognitive empathy, while affective empathy is less affected, indicating more research is needed.…”
Section: Alexithymic Traits and Facial Emotion Recognitionmentioning
confidence: 99%
“…Both personality traits are suggested to be associated with empathy related deficits, which are thought to result from different impairments during the empathy process [3]. While psychopathic traits are often related with deficits in predominantly affective empathy [40,41], that is documented with a specific deficit in the recognition of distressed facial expressions, alexithymic traits show intact affective empathy [58,59] but deficits with cognitive empathy [35,57] that are presented as a generalized deficit for all emotions. Individuals with alexithymic traits seem to struggle to represent emotional states in themselves, that leads to deficits in correctly identifying emotions in others [56].…”
Section: The Current Studymentioning
confidence: 99%
“…It has been argued that a set of skills are impaired in bullying: interpersonal skills, such as empathy and moral disengagement, coping strategies and management of stress, emotional expression and regulation [ 2 ]. Recently, Sen Demirdogen et al [ 3 ] have reported that bullying among Turkish adolescents was significantly associated with lower levels of “reading minds in the eyes”, alexithymia traits as well as lower empathy. In particular, alexithymia, emotional components of alexithymia, as well as anger-expression styles, have been described as associated factors to bullying, cyberbullying, victimization and their perpetration [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%